2020
DOI: 10.3892/etm.2020.9070
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of�Rho‑kinase is involved in the therapeutic effects of atorvastatin in heart ischemia/reperfusion

Abstract: The aim of the present study was to investigate the effects of atorvastatin against heart ischemia/reperfusion (I/R) injury and its potential underlying mechanism. Rats were allocated into the following groups: Sham, I/R, atorvastatin (10 mg/kg daily), fasudil (10 mg/kg daily) and atorvastatin + fasudil in combination. Drugs were administered for 2 weeks prior to I/R injury. I/R was established by ligating the left anterior descending branch (LAD) for 30 min and releasing the ligature for 180 min. The I/R grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In model rats, atorvastatin therapy significantly lowers plasma CK-MB and lactate dehydrogenase levels ( 28 ). Moreover, pretreatment with atorvastatin significantly reduces plasma IL-6 and TNF-α levels as well as Rho-kinase activity, myocardial infarct size, and cardiomyocyte apoptosis ( 29 ). Studies have shown that the intestinal microflora is altered during the development and treatment of various diseases, and participates in numerous physiological processes, including the inflammatory response, and energy and nutrient metabolism ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In model rats, atorvastatin therapy significantly lowers plasma CK-MB and lactate dehydrogenase levels ( 28 ). Moreover, pretreatment with atorvastatin significantly reduces plasma IL-6 and TNF-α levels as well as Rho-kinase activity, myocardial infarct size, and cardiomyocyte apoptosis ( 29 ). Studies have shown that the intestinal microflora is altered during the development and treatment of various diseases, and participates in numerous physiological processes, including the inflammatory response, and energy and nutrient metabolism ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…MDA is a widely used oxidant parameter in oxidative stress-induced LPO [22]. Actually, the studies have reported that atorvastatin inhibits MDA and proinflammatory cytokine production and protects heart tissue from ischemia-reperfusion injury [23]. Another experimental study designed with cadmium chloride, atorvastatin treatment prevented oxidative liver tissue damage [24].…”
Section: Discussionmentioning
confidence: 99%
“…CKD, chronic kidney disease; GDF- Statins induce eNOS upregulation (increase eNOS mRNA stability) and thereby increase NO bioavailability (Figure 2) [30]. This effect may be achieved through the inhibition of the Rho/ROCK pathway [31] and the activation of PI3K/protein kinase Akt pathway [31]. In endothelial cells, ROCKs inhibit the pro-survival PI3K/protein kinase Akt pathway, resulting in decreased eNOS expression and cGMP levels [32].…”
Section: Microcirculatory Endothelial Dysfunction In Hfpef and Endoth...mentioning
confidence: 99%